Barriers to, and enablers of, paramedics responding to suspected or confirmed COVID-19 cases: An integrative review. (March 2023) - Howarth, Ursula; Zimmerman, Peta-Anne; van de Mortel, Thea; Barr, Nigel
Abstract: Background: The coronavirus pandemic (COVID-19) has focused attention on healthcare workers' concerns about working during a pandemic, yet research on the effect of the pandemic specifically on paramedics is lacking. This literature review aims to critically examine the current knowledge of paramedics' experience of barriers to, and enablers of, responding to suspected or confirmed COVID-19 cases. Methods: An integrative review was undertaken using articles found by a systematic search of four research databases. Inclusion criteria included paramedics or emergency medical technicians who had experience of barriers or enablers responding to patients during the coronavirus pandemic. Results: Nine articles met the inclusion and exclusion criteria. Barriers included communication and poor leadership, fear of infection to self and family, frequent changes in guidelines and inconsistencies across agencies, stress/burnout, and concerns with personal protective equipment. Enablers included job security, perceived social support, solidarity with other paramedics, and use of modern technologies for communication. Conclusions: There are unique experiences of working during the COVID-19 pandemic in the prehospital environment. Particular challenges occurred with leadership, communication within the organisation and between agencies, and working in an unpredictable environment.